Penerapan Reciprocal Teaching Untuk Meningkatkan Berpikir Kritis Dan Kemandirian Belajar Siswa MA - Hidayat, Dayat (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
The purpose of this study is to know: 1) How the application of reciprocal teaching approach can increase the ability of critical thinking and self-regulated learning; 2) whether there is a relationship between the ability to think critically self-regulated learningwith reciprocal teaching approach. This research is implemented Madrasah Aliyah Negeri Bandung Barat with the population are all MA students in West Bandung regency. The method used in this research is Quasi Eksperimen where there are two classes that one class by using reciprocal teaching and one class again using ordinary learning. The study design was a non-randomized control-treatment group, pretest-posttest design. The population of this study was all students in West Bandung regency and the sample subjects were two classes in MAN Bandung Barat with the total number of 72 students, 1Â as experiment class and one class as control class. The results of research to improve learning ability by using reciprocal teaching and cognitive learning ability with student learning independence with the reciprocal teaching approachKeywords: reciprocal teaching approach, critical thinking, self-regulated learning.The purpose of this study is to know: 1) How the application of reciprocal teaching approach can increase the ability of critical thinking and self regulated learning; 2) whether there is a relationship between the ability to think critically self regulated learningwith reciprocal teaching approach. This research is implemented Madrasah Aliyah Negeri Bandung Barat with the population are all MA students in West Bandung regency. The method used in this research is Quasi Eksperimen where there are two classes that one class by using reciprocal teaching and one class again using ordinary learning. The study design was a non-randomized control-treatment group, pretest-posttes design. The population of this study were all students in West Bandung regency and the sample subjects were two classes in MAN Bandung Barat with total number of 72 students, 1 class as experiment class and one class class as control class. The results of research to improve learning ability by using reciprocal teaching and cognitive learning ability with student learning independence with reciprocal teaching approach.Â Keywords: reciprocal teaching approach, critical thinking, self regulated learning.